In the Thicket of Cultural Discourses (KULT_online, 2009)
With the publication of her thesis, sociologist Rebecca Belvederesi aims to systematically describe discourses of cultural identity in a post-colonial context. Having studied sociology, philosophy, social and economic history, Belvederesi makes use of various "sociological theories" to explore questions of cultural identity that have occupied historically colonial powers for decades and caused the emergence of post-colonial studies throughout the English diaspora, but have only recently exploded in Germany, where lively debate about a Leitkultur indicates a new desire for self-positioning and -definition. It is in this context that Belvederesi intends to systematically reconstruct post-colonial identity discourses and make them amenable for investigations of cultural identity in Germany – an objective that she is ultimately unable to fulfil.